Plant secondary metabolite and glycosyltransferases - Altanzul, Khorolragchaa (Proceedings of the Institute of Biology, 2023)
Glycosylation is the last step in the biosynthesis of the secondary metabolite. The glycosylation process is catalyzed by glycosyltransferase (GTs), which are highly divergent and polyphyletic and belong to a multigene family in plant organisms. Among them, the GT family 1 is the largest, often referred to as UDP-glycosyltransferases (UGTs) and catalyzes the transfer of a glycosyl moiety from UDP sugars to a diverse array of substrates, including hormones, secondary metabolites, and xenobiotics such as pesticides and herbicides. UGTs play an essential role in stabilizing, enhancing water solubility, and deactivating/ detoxifying natural products, leading to regulating metabolic homeostasis, detoxifying xenobiotics, and the biosynthesis, storage, and transport properties of secondary metabolites. In this review, we include the classification, nomenclature, and sequence homology of glycosyltransferases and summarize their roles in plant defense mechanisms, detoxification, secondary metabolite biosynthesis, and hormone regulation with examples from some studies conducted in plants. Knowing more about the function and mechanism of this gene in the organism will be essential to discover its industrial and scientific importance in the future. It is a significant topic in the pharmaceutical industry, especially as it plays a critical role in the synthesis of secondary metabolites and the defense system of plants. Ургамлын хоёрдогч метаболит ба гликозилтрансферазууд Хураангуй. Гликозиляцийн процесс нь хоёрдогч метаболитын бионийлэгжлийн хамгийн сүүлийн шат юм. Гликозиляцийн процессыг гликозилтрансфераза (GTs) хурдасгадаг бөгөөд тэдгээр нь олон ялгаатай, полифилетик шинж чанартай бөгөөд ургамлын маш том бүлэг ген юм. Тэдгээрийн дотроос GT 1-р бүлэг хамгийн том нь бөгөөд ихэвчлэн UDP-гликозилтрансфераза (UGTs) гэж нэрлэгддэг ба UDP сахараас гликозилийн хэсгийг гормон, хоёрдогч метаболит, ксенобиотик зэрэг олон төрлийн субстрат уруу шилжүүлдэг катализаторын үүрэг гүйцэтгэдэг. UGT нь байгалийн гаралтай бүтээгдэхүүнийг тогтворжуулах, усанд уусах чадварыг сайжруулах, идэвхгүйжүүлэх/ хоргүйжүүлэхэд чухал үүрэг гүйцэтгэдэг бөгөөд энэ нь бодисын солилцооны гомеостазыг зохицуулах, ксенобиотикийг хоргүйжүүлэх, хоёрдогч метаболитуудын бионийлэгжил, хадгалалт, зөөвөрлөлтийг зохицуулахад оролцдог. Энэхүү тоймд бид гликозилтрансферазын ангилал, нэршил, дарааллын гомологи зэргийг багтаахын зэрэгцээ ургамлын хамгааллын механизм, хоргүйжүүлэлт, хоёрдогч метаболитын бионийлэгжил, дааврын зохицуулалт зэрэгт тэдгээрийн гүйцэтгэх үүргийг ургамалд хийсэн зарим судалгааны жишээн дээр нэгтгэн харуулав. Энэхүү бүлэг генийн организмд , ялангуяа хоёрдогч метаболитуудын нийлэгжилт, ургамал хамгааллын системд гүйцэтгэх үүрэг, механизмын талаар илүү ихийг мэдэх нь шинжлэх ухаанд чухал ач холбогдолтойгоос гадна ирээдүйд түүний үйлдвэрлэлд тус дэм болох юм. Түлхүүр үгс: гликозиляци, UDP-аас хамааралтай гликозилтрансфераза, PSPG мотиф